Arbuscular mycorrhizal fungi as a biological soil management practice for regulating soil carbon dynamics in agricultural soils: A global meta-analysis - Huawei Yang; Yuhang Zhang; Dingyi Liu; Yue Fan; Diwei Song; Pengju Li; Jingdan Yang; Xiaozhe Ma; Ruixin Bi; Shumin Li; Lingbo Meng (Soil and Tillage Research, 2026)

Non-destructive citrus freshness assessment by Raman spectroscopy exploiting oil and non-oil gland heterogeneity - Shumin Gao; Rongxuan Wu; Wen Zhang; Zhiqing Yang; Haofan Zhang; Min Chen; Shanjun Li (Postharvest Biology and Technology, 2026)

Meteorological regime controls on PM2.5 and O3 variability in the Sichuan Basin: insights from a hybrid causal-machine learning analysis - Yuyi Du; Xin Qi; Miao Feng; Hanxiong Che; Fumo Yang; Xin Long; Dasheng Huang; Shumin Zhang; Chao Peng; Yang Chen (Atmospheric Environment, 2026)

Ultimate removal of refractory organics in coking wastewater by integrated sustainable oxidation and adsorption processes - Yunxing Dong; Lili Zhang; Weihan Tian; Lele Gao; Shumin Li; Yingxin Gao; Min Yang (Journal of Environmental Sciences, 2026)

Role of galloyl moiety in modulating the interaction between Cyperus esculentus protein and tea polyphenols: A structure-activity relationship - Liping Qin; Shumin Yu; Puying Chen; Luoqing Ding; Chunming Zou; Xi Yang; Xuebo Liu; Lijun Sun (Food Chemistry, 2026)

Interfacial and emulsifying properties of low-denatured soy protein prepared by self-coacervation - Shumin Zhang; Jiyang Cai; Zhuojia Lin; Chang Yang; Zhihong Lyu; Menghui Wang; Wentao Qian; Zhili Wan; Hongliang Li; Xiaoquan Yang (Food Hydrocolloids, 2026)

Diurnal variations of organic molecules in atmospheric PM2.5 in urban areas of the Yangtze River Basin, China characterized by UHPLC–Orbitrap MS - Xin Ou; Lijuan Li; Xin Qi; Jiawei Zhou; Hanxiong Che; Zhier Bao; Yiliang Liu; Lingshuo Meng; Xin Long; Xiaojiang Yao; Shumin Zhang; Yang Chen (Atmospheric Environment, 2026)

Concentration and depth-resolved analysis of transition metals in atmospheric particles: A combined approach using X-ray fluorescence and synchrotron radiation single-particle imaging - Yiliang Liu; Jiawei Zhou; Hanxiong Che; Difei Zhang; Pingping Wen; Yifan Zhao; Xin Du; Lingshuo Meng; Yan Han; Zhier Bao; Xin Qi; Xin Long; et al. (Journal of Environmental Sciences, 2026)

Infant-derived bifidobacterium can enhance the ability to respond to influenza virus infection by promoting type I interferon-mediated immunity - Jiaqian Shentu; Qinggang Xie; Minghui Yan; Shumin Wang; Xiaoxuan Sun; Chengcheng Zhang; Peijun Tian; Xiaomei Lv; Bo Yang; Wenwei Lu; Shumao Cui; Gang Wang; et al. (Food Bioscience, 2026)

Mechanisms of water-state transition and hydrophobicity evolution of organics during ultrasonic dewatering of algal sludge - Shumin Yang; Li-an Hou; Rongsheng Ning; Xinyuan Yi; Shuili Yu; Yulin Tang (Environmental Research, 2026)

Decoding the Oxytocinergic and Behavioral Signatures of Milk Ejection - Wei Xiao; Qian Zheng; Yang Wang; Ying Yuan; Yuge Chen; Tianxing Zheng; Yuzhu Chen; Yijia Gao; Bingrui Song; Bin Zhang; Liyao Qiu; Linghui Zeng; et al. (Neuroscience Bulletin, 2026)

Phytochemicals from the leaves of Staphylea arguta (Turpiniae Folium) and their anti-inflammatory activity - Shumin Wu; Feifei Tang; Xiyu Xu; Xiaoxiang Fan; Danting Luo; Yunqing He; Ping Hai; Shengxiang Yang; Yuan Gao; Jian Yang (Natural Product Research, 2026)

β-Sitosterol: a Common Compound in Hundreds of Traditional Chinese Medicine Treatments for Infertility and its Effects on Human Ovarian Granulosa Cells - Yu Sun; Gengchen Feng; Ziyi Yang; Yimeng Li; Shumin Li; Shigang Zhao (Phenomics, 2026)

Construction of Pt-TiOx interfacial sites via Pt-TiO2 metal-support interaction for efficient catalytic dehydrogenation of methylcyclohexane - Zhengjian Li; Mingzhi Wang; Shumin Liu; Huayue Yang; Yun Zhao; Lin Gu; Guangxu Chen (Science Bulletin, 2026)

Variations of Corticotropin-Releasing Factor Receptor 1α Contribute to the Blunted HPA Axis Responses to Hypoxia in Plateau Mammals - Jiafang Yang; Fangyuan Xia; Hao Jin; Chatoo Mahanand; Huiqi Lin; Yibin Cao; Jianghui Bian; Dengbang Wei; Eviatar Nevo; Jizeng Du; Shumin Duan; Fang Guo; et al. (Neuroscience Bulletin, 2026)

Immune‐Inflammatory Imbalance in Mice Under High Humidity and Three Different Ambient Temperatures: Insights From Gut Microbiome and Serum Metabolomics - Hua Yang; Shumin Wei; Xiaomin Ou; Wei Jiang; Weihui Lu; Taohua Lan (Environmental Microbiology, 2026)
Gut microbiota and metabolites have been increasingly implicated in the pathogenesis of immune inflammation, which may be affected by environmental factors. This study aimed to explore the influence of co‐exposure to high humidity and temperatures (low, normal or high) on biomarkers of immune inflammation and potential mechanisms. We established C57BL/6J mice models (with equal numbers of males and females) of high humidity and low temperature (HH‐LT), normal temperature (HH‐NT) or high temperature (HH‐HT) co‐exposure environments to observe the impact of high humidity and different temperature co‐exposure environments for 28 and 56 consecutive days. Following exposure, results showed that all six combined exposure conditions significantly increased pro‐inflammatory cytokines (TNF‐α, IL‐1β, IL‐12p70), decreased anti‐inflammatory cytokines (IL‐4, IL‐10) and elevated the Teff/Treg ratio in the spleen. Gut microbiota analysis revealed reduced Akkermansia and increased Desulfovibrio and Enterorhabdus . Serum metabolomics identified widespread disturbances enriched in pathways including protein digestion and absorption, lysine degradation, phenylalanine metabolism and unsaturated fatty acid biosynthesis. Pearson correlation analysis confirmed significant associations among microbial shifts, immune‐inflammatory dysregulation and metabolic perturbations—suggesting that high humidity combined with different temperatures correlated with immune imbalance, likely mediated by gut dysbiosis and serum metabolic disruption.

Microbial functional decay coupled with adsorption loss in biologically activated carbon: Machine learning driven dual-indicator framework for precise replacement - Yongjie Huang; Xiaoyao Weng; Lingfei Zhang; Shumin Yang; Weiwei Zhang; Yulin Tang; Yongji Zhang (Journal of Environmental Chemical Engineering, 2026)

Multi-pathway vegetation restoration drives differential carbon sequestration regulated by hydrogeological conditions in Lijiang River Basin - Shumin Feng; Xiuqin Wu; Jianhua Cao; Hui Yang; Fen Huang; Liankai Zhang; Jinxing Zhou (CATENA, 2026)

Mechanisms of flavonoid-mediated amelioration of MASLD: flavonoids, their metabolites or impact on gut microbes? - Ruxuan Chen; Xionghui Wu; Ning Yin; Enjun Xie; Shumin Sun; Jie Shen; Yunmei Chen; Fenghua Zhou; Tao Li; Qili Li; Donglin Su; Fuhua Fu; et al. (Critical Reviews in Food Science and Nutrition, 2026)

Effective degradation of aflatoxin B1 and zearalenone by a recombinant laccase from Heyndrickxia shackletonii - Fred Mwabulili; Peng Li; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma; Xiao Li; Hang Jia; Yanli Xie (World Journal of Microbiology and Biotechnology, 2026)

Emerging cancer electrotherapeutic technologies: a biomedical engineering paradigm - Yichi Cai; Shumin Sun; Jihu Nie; Nailin Yang; Liang Cheng (Science Bulletin, 2026)

Synergistic coupling of ultrasonic activation and BaTiO3 piezoelectric ceramic membranes for robust algae-water separation: Dynamics of foulant migration and radical oxidation - Shumin Yang; Li-an Hou; Xinyuan Yi; Yongjie Huang; Qianli Zhang; Shuili Yu; Yulin Tang (Journal of Environmental Chemical Engineering, 2026)

Effects of photochemical and aqueous-phase oxidation on secondary formation during the 31st FISU Summer World University Games, 2023 - Xiaoling Zeng; Zhier Bao; Jiawei Zhou; Guangming Shi; Li Zhou; Shumin Zhang; Xin Qi; Keding Lu; Chongzhi Zhai; Zhenliang Li; Xin Li; Chao Peng; et al. (Journal of Environmental Sciences, 2026)

Tracing the geographical origin of tiger nut (Cyperus esculentus L) in China based on stable isotopes and mineral elements combined with multi-modal recognition - Sun Shumin; Wang Nanxi; Sun Tiantian; Luo Xiaohong; Yang Yongtan (Food Chemistry, 2026)

Fine-mapping and candidate gene analysis of qFF3.1 conferring fruit firmness in a modern tomato variety - Yunhao Han; Xin Li; Can Zhu; Yonglian Wang; Junling Hu; Shumin He; Saifeng Guo; Xiaoxiao Lu; Chunyang Pan; Zejun Huang; Yanmei Guo; Xiaoxuan Wang; et al. (Theoretical and Applied Genetics, 2026)

The promoter sequence of (-)-limonene synthase in Mentha Canadensis and its strong activity in the glandular trichome and in the stomatal guard cells - Shumin Li; Zhichao Xue; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Xu Yu; Chengyuan Liang (Acta Physiologiae Plantarum, 2026)

The immunosuppressive receptor FcγRIIb (CD32b) gets involved in immune response of Nile Tilapia (Oreochromis niloticus) against bacterial infection - Jiadong Li; Shumin Du; Qingliang Zeng; Zhanyao Lin; Yansong Wang; Lu Deng; Xiaoxue Yin; Yanjian Yang; Zheng Guo; LiangLiang Mu; Jianmin Ye (Aquaculture, 2026)

Enhanced effect and mechanism of biochar on the nitrogen removal of low C/N wastewater by cold-tolerant heterotrophic nitrifying–aerobic denitrifying bacterium - Xiaoyu Li; Meizhen Tang; Jie Jiang; Shiqiang Ma; Shumin Yao; Yuewei Yang (Journal of Contaminant Hydrology, 2026)

Environmental interactions drive soil organic and inorganic carbon distributions in Southeast China’s mangrove restoration areas - Shuya Xie; Xianglan Li; Zhe Xu; Zhongpeng Ma; Zhao Zhang; Shumin Zhang; Yahui Chen; Minghai Xu; Wei Chen; Sheng Yang; Qiuxia Chen; Xing Liu (CATENA, 2026)

Targeting Strategies of Stem Cell-Derived Extracellular Vesicles in the Treatment of Cardiovascular Diseases - Jiaming Fan; Liyun Yao; Jiayi Yao; Shumin Jiang; Lianbo Shao; Yunfang Mo; Ziying Yang; Zhenya Shen (Stem Cell Reviews and Reports, 2026)

Spatially-confined bubble plasma oxidation induced by microchannel discharge to boost energy efficiency in water treatment - Shumin Li; Bangdou Huang; Yingxin Gao; Yunxing Dong; Qi Wang; Lili Zhang; Cheng Zhang; Jianwei Yu; Min Yang (Water Research, 2025)

Metagenomic insights into carbon–nitrogen metabolism of heterotrophic nitrification–aerobic denitrification bacteria utilizing different biodegradable polymers - Huan Liu; Chenxi Yang; Shumin Qin; Qian Zhang (Environmental Research, 2025)

Potential new drug sources for the treatment of Parkinson’s disease: flavonoid O-glycosides - Yehao Wang; Jinjin Yang; Xin Jiang; Runda Yuan; Ruyang Cheng; Ningxia Lu; Ao Gao; Shumin Liu (Molecular Biology Reports, 2025)

Effects of a dietary liquid extract of Lentinus edodes on the growth performance, immune traits, and intestinal flora of weaned Simmental calves - Mengqi Wang; Yi Yang; Jing Yang; Junlong Bi; Yongjun Zhao; Sirui Wang; Haixia Guo; Shumin Sun (Animal Feed Science and Technology, 2025)

pH-responsive microgels constructed from soy protein coacervates: Structure and rheology at the oil-water interface - Jiyang Cai; Shumin Zhang; Sili Liu; Xiang Li; Zhili Wan; Boris A. Noskov; Xiaoquan Yang (Food Hydrocolloids, 2025)

An integrated hydrothermal and ball-milling approach for the co-production of glucose, xylose and residual lignin from Moso bamboo - Qianying Yang; Chen Zhang; Lili Shang; Jialong Wen; Shumin Yang (Bioresource Technology, 2025)

Air pollution-related mortality and contributing factors in Chengdu: insights from a Basin City bordering the Qinghai-Tibet Plateau - Xin Nie; Ping Shao; Xianyu Yang; Meng Xiu; Chaoyong Tu; Shumin Chen; Zhigang Wu; Siyuan Wang; Yu Hao; Shigong Wang (Environmental Geochemistry and Health, 2025)

Vegetation-hydrology coupling drives spatiotemporal dynamics of soil organic carbon sequestration in the northernmost restored mangrove areas in southern China - Shuya XIE; Xianglan LI; Meijie ZHU; Yang GUO; Zhao ZHANG; Shumin ZHANG; Yahui CHEN; Zhe XU; Pengpeng TIAN; Yuting HUANG; Churui GUAN (Pedosphere, 2025)

Carbon sequestration in soil affected by mineral-doped biochar: Roles of soil aggregate and microbial community - Rongchuan Ye; Yan Ma; Zixuan Wang; Ting Yang; Yanbin Du; Shumin Wu; Yanfang Feng; Lisha Wang; Wenjing Song (Journal of Cleaner Production, 2025)

Unlocking novel angiotensin-converting enzyme inhibitory peptides from Nili Ravi buffalo milk β-casein: A synergistic strategy combining targeted hydrolysis, 3D-QSAR modeling, and mechanistic insights - Jionghui Gu; Shumin Yue; Xin Yang; Zuyi Lu; Zhaorui Wang; Xuechun Wei; Liqin Zhou; Zhenxia Zhao; Zhongfeng Shi; Zhongxing Zhao (Food Bioscience, 2025)

Enhanced winter performance of constructed wetlands via biochar-immobilized Psychrotrophic bacteria - Xiaoyu Li; Meizhen Tang; Shumin Yao; Shiqiang Ma; Yuewei Yang (Journal of Water Process Engineering, 2025)

Establishment of the Diagnostic Signature of Ferroptosis Genes in Multiple Sclerosis - Yang Yang; Qianqian Bai; Fangfei Liu; Shumin Zhang; Wenchao Tang; Ling Liu; Zhehua Xing; Hao Wang; Chi Zhang; Yanhui Yang; Hua Fan (Biochemical Genetics, 2025)
Ferroptosis is a novel form of membrane-dependent cell death that differs from other cell death modalities such as necrosis, apoptosis, and autophagy. Multiple sclerosis (MS) is a chronic inflammatory disease of the central nervous system primarily affecting brain and spinal cord neurons. Although the pathogenesis of these two conditions may seem unrelated, recent studies have indicated a connection between ferroptosis and multiple sclerosis. In fact, ferroptosis plays a significant role in the development of MS, as evidenced by the presence of elevated iron levels and iron metabolism abnormalities in the brains, spinal cords, and other neurons of MS patients. These abnormalities disrupt iron homeostasis within cells, leading to the occurrence of ferroptosis. However, there is currently a lack of research on the diagnostic value of ferroptosis-related genes in multiple sclerosis. In this study, we employed bioinformatics methods to identify ferroptosis-related genes ( ATM, GSK3B, HMGCR, KLF2, MAPK1, NFE2L1, NRAS, PCBP1, PIK3CA, RPL8, VDAC3 ) associated with the diagnosis of multiple sclerosis and constructed a diagnostic model. The results demonstrated that the diagnostic model accurately identified the patients’ condition. Subsequently, subgroup analysis was performed based on the expression levels of ferroptosis-related genes, dividing patients into high and low expression groups. The results showed differences in immune function and immune cell infiltration between the two groups. Our study not only confirms the correlation between ferroptosis and multiple sclerosis but also demonstrates the diagnostic value of ferroptosis-related genes in the disease. This provides guidance for clinical practice and direction for further mechanistic research.

Glutathione responsive curcumin delivery via amino acid covalently grafted cyclodextrin metal organic framework coated with soy hull polysaccharides - Shumin Wang; Shengnan Wang; Xiuzhi Cao; Lina Yang; He Liu (Food Chemistry, 2025)

Promotion of maize straw degradation rate by altering microbial community structure through the addition of soybean straw - Xiaodan Liu; Hongrui Huo; Yuhang Zhang; Huawei Yang; Shumin Li; Lingbo Meng (Plant and Soil, 2025)

Targeted ecological risk, morphological structure and driving forces of sediment metals under anthropogenic stress - Shumin Fang; Chunyu Hua; Jiaying Yang; Feifei Liu; Lei Wang; Dongyue Wu; Yuyao Wang; Lijun Ren (Process Safety and Environmental Protection, 2025)

Cellular uptake and transport mechanism of flaxseed cyclic peptide CLB via clathrin-dependent endocytosis - Xianguo Zou; Miao Zheng; Yuqin Cao; Shumin Zou; Yuwan Nie; Zeyuan Deng; Yahya S. Hamed; Kai Yang (Food Research International, 2025)

The CPDG treatment and dose-dependent effects of zein-stevioside conjugates on formation, drainage behavior, and interfacial structure of Pickering foam - Zihan Qu; Tongliang Yang; Yushan Wang; Shumin Zhang; Zhili Wan; Shuhong Li; Ye Chen; Guiyun Chen (Food Chemistry, 2025)

Sources and light absorption of brown carbon in urban areas of the Sichuan Basin, China: Contribution from biomass burning and secondary formation - Chao Peng; Mi Tian; Guangming Shi; Shumin Zhang; Xin Long; Hanxiong Che; Jie Zhong; Xiangyu You; Zhier Bao; Fumo Yang; Xin Qi; Chongzhi Zhai; et al. (Atmospheric Research, 2025)

Degradation of patulin in aqueous solution and apple juice by titanium dioxide/graphitic carbon nitride: efficiency, quality and safety - Shumin Sun; Mengdan Ku; Jiayi Yang; Wenhao Zhang; Yanli Xie (Food Additives & Contaminants: Part A, 2025)

Comparison of the start-up of rotating biofilm contactor reactor with HN-AD bacteria inoculation under high and low influent ammonia conditions - Shumin Qin; Yan Lin; Chenxi Yang; Qian Zhang (Journal of Environmental Management, 2025)

Spatiotemporal analysis of the coupling and decoupling relationship between urbanization and atmospheric environment in the Yellow River Basin of China - Feifei Liu; Mengyuan Zhu; Chunyu Hua; Lei Wang; Yueru Tian; Shumin Fang; Jiaying Yang; Lijun Ren (Theoretical and Applied Climatology, 2025)

Variation characteristics and impact factors of the co-occurrence of surface ozone and particulate matter over the Southern Sichuan region, China - Ping Shao; Siyuan Wang; Chaoyong Tu; Shumin Chen; Xianyu Yang; Shenglan Zeng; Jin Fan; Shaobo Zhang; Changjian Ni; Shigong Wang (Natural Hazards, 2025)

Risks of respiratory and circulatory system diseases induced by exposure to PM2.5 in high humidity and low solar radiation environments: disease types, genes, and functions - Xiaomeng Li; Liru Zhang; Zhengliang Zhang; Xuan Li; Jingli Qian; Jiawei Zhou; Hanxiong Che; Yan Han; Xin Qi; Fumo Yang; Yu Huang; Chao Peng; et al. (Environmental Geochemistry and Health, 2025)

Effect of rotational speed on nitrogen removal performance and microbial community characteristics of the rotating biological contactor pure biofilm system inoculated with heterotrophic nitrification-aerobic denitrification bacteria - Shumin Qin; Wang Chen; Chenxi Yang; Qingping Tang; Qian Zhang (Journal of Environmental Chemical Engineering, 2025)

Solid membrane-based aqueous lithium extraction and adsorption: Advances, challenges, and prospects - Yueru Yang; Shumin Bi; Faquan Wang; Xinyu Pan; Tianci Yang; Shui Hu; Shuting Tang; Qingxiu Jia (Chemical Engineering Journal, 2025)

Correlation between pollen morphology, karyotype, floral pigments, and scent components and morphological classification of 15 species and hybrids of Syringa L - Feng Qian; Xiaoou Zhai; Ziyin Cheng; Zhenyu Yu; Guoqiang Chen; Yan Gao; Liwei Sun; Li Fang; Shumin Yang; Shaoqi Xu; Huimin Liu (The Science of Nature, 2025)

Dongting Lake algal bloom forecasting: Robustness and accuracy analysis of deep learning models - Yuxin Liu; Bin Yang; Kunting Xie; Julong Sun; Shumin Zhu (Journal of Hazardous Materials, 2025)

Combined pollution of soil by heavy metals, microplastics, and pesticides: Mechanisms and anthropogenic drivers - Shumin Fang; Chunyu Hua; Jiaying Yang; Feifei Liu; Lei Wang; Dongyue Wu; Lijun Ren (Journal of Hazardous Materials, 2025)

An electrically activable nanochip to intensify gas-ionic-immunotherapy - Gang Wang; Jingrui Li; Shumin Sun; Yuqi Yang; Zhihui Han; Zifan Pei; Liang Cheng (Science Bulletin, 2025)

Multistep dynamic wetting of soy protein coacervates at hydrophobic interfaces - Jiyang Cai; Shumin Zhang; Shuqin Zheng; Yunyi Yang; Zhili Wan; Xiaoquan Yang (Food Hydrocolloids, 2025)

Expression, characterization, and application of an aldo-keto reductase mined from Bacillus velezensis Vel-HNGD-F2 for deoxynivalenol biodegradation - Junxia Liu; Peng Li; Xiao Li; Yanli Xie; Fred Mwabulili; Shumin Sun; Yuhui Yang; Weibin Ma; Qian Li; Hang Jia (Food and Chemical Toxicology, 2025)

Characteristics and health risks assessment of PM2.5-bound heavy metals during winter in urban areas of northern China: A case study in Kaifeng - Xin Qi; Yan Han; Hanxiong Che; Jiawei Zhou; Chao Peng; Zhier Bao; Yiliang Liu; Lingshuo Meng; Shumin Zhang; Fumo Yang; Wenbo Xue; Yu Lei; et al. (Science of The Total Environment, 2024)

Lung cell injury risks of PM2.5 exposure in the high humidity and low solar radiation environment of southwestern China - Qin Zhang; Xuan Li; Xiaomeng Li; Ronghua Zhang; Bi Ren; Hanxiong Che; Xin Qi; Jiawei Zhou; Jiancai Tang; Andre S.H. Prevot; Zhenzhong Liu; Li Jiang; et al. (Atmospheric Environment, 2024)

Research diversity and advances in simultaneous removal of multi-mycotoxin - Fred Mwabulili; Peng Li; Jinghao Shi; Hongxin Zhang; Yanli Xie; Weibin Ma; Shumin Sun; Yuhui Yang; Qian Li; Xiao Li; Hang Jia (Toxicon, 2024)

Transcriptional regulation and functional validation analysis of the McbZIP1 in Mentha canadensis L. - Xu Yu; Shumin Li; Taolan Xiao; Xiwu Qi; Hailing Fang; Li Li; Yang Bai; Dongmei Liu; Qun Liu; Zequn Chen; Zhichao Xue; Chengyuan Liang (Plant Science, 2024)

Identification of the effects of low temperature on grain-setting rate of different types of late-season rice (Oryza sativa) during heading - Yibo Gao; Yi Li; Ling Huang; Jinsong Zhao; Shumin Li; Jianxin Lu; Xinghua Li; Tewu Yang (Field Crops Research, 2024)

Nucleus Accumbens Corticotropin-Releasing Hormone Neurons Projecting to the Bed Nucleus of the Stria Terminalis Promote Wakefulness and Positive Affective State - Gaojie Pan; Bing Zhao; Mutian Zhang; Yanan Guo; Yuhua Yan; Dan Dai; Xiaoxi Zhang; Hui Yang; Jinfei Ni; Zhili Huang; Xia Li; Shumin Duan (Neuroscience Bulletin, 2024)
The nucleus accumbens (NAc) plays an important role in various emotional and motivational behaviors that rely on heightened wakefulness. However, the neural mechanisms underlying the relationship between arousal and emotion regulation in NAc remain unclear. Here, we investigated the roles of a specific subset of inhibitory corticotropin-releasing hormone neurons in the NAc (NAc CRH ) in regulating arousal and emotional behaviors in mice. We found an increased activity of NAc CRH neurons during wakefulness and rewarding stimulation. Activation of NAc CRH neurons converts NREM or REM sleep to wakefulness, while inhibition of these neurons attenuates wakefulness. Remarkably, activation of NAc CRH neurons induces a place preference response (PPR) and decreased basal anxiety level, whereas their inactivation induces a place aversion response and anxious state. NAc CRH neurons are identified as the major NAc projection neurons to the bed nucleus of the stria terminalis (BNST). Furthermore, activation of the NAc CRH -BNST pathway similarly induced wakefulness and positive emotional behaviors. Taken together, we identified a basal forebrain CRH pathway that promotes the arousal associated with positive affective states.

GWSM4C: A global wave surrogate model for climate simulation based on a convolutional architecture - Quan Jin; Xingjie Jiang; Feng Hua; Yongzeng Yang; Shumin Jiang; Chen Yu; Zhenya Song (Ocean Engineering, 2024)

Interaction between basement detachment fault, rift onset unconformity, and overlying basin fills: An example from the Songliao basin of a Cretaceous active continental margin volcanic rift in northeast Asia - Pujun Wang; Zhuolong Yang; Youfeng Gao; Xuejiao Qu; Haibo Liu; Yongkang Yin; Chengshan Wang; Xiaoqiao Wan; Shumin Chen (Marine and Petroleum Geology, 2024)

Identification of microbiological genomes carrying antibiotic resistance genes and virulence factor genes for microbiological risk assessment in filter backwash water - Yongjie Huang; Xiaoyao Weng; Xinlu Qu; Tianxiao Sun; Weiwei Zhang; Shumin Yang; Xin He; Yuan Xiao; Tianyang Zhang; Yulin Tang (Journal of Environmental Chemical Engineering, 2024)

pH-responsive Aminated mesoporous silica microspheres modified with soybean hull polysaccharides for curcumin encapsulation and controlled release - Shumin Wang; Shengnan Wang; Lina Yang; Peng Wang; Hong Song; He Liu (Food Chemistry, 2024)

Use of modified poly-epoxysuccinic acid as an efficient scale inhibitor to control CaSO4 scaling in NF processes: Performance and mechanisms - Xinyuan Yi; Shumin Yang; Xin He; Zhiwei Wang; Min Rui; Yulin Tang (Desalination, 2024)

No Association of Polycystic Ovary Syndrome with Pancreatic Cancer: A Mendelian Randomization Study - Xueying Gao; Yuteng Wang; Yikun Wang; Ziyi Yang; Xueqi Yan; Shumin Li; Yonghui Jiang; Yimeng Li; Shigang Zhao; Han Zhao; Zi-Jiang Chen (Phenomics, 2024)

The impact of aeration rate on the denitrification performance and microbial community characteristics of the HN-AD bacteria-inoculated MBBR system - Qian Zhang; Chenxi Yang; Shumin Qin; Peng Zhang; Yu Hu; Huacan Tian; Baiying Liu; Haiying Chen; Wei Li (Journal of Water Process Engineering, 2024)

Preparation of Ultra-Sensitive flexible temperature sensors with thermal responsive waterborne polyurethane for enhanced temperature sensing performance - Chenguang Kong; Xiaobin Li; Jun Shi; Hangzhou Wang; Cunzhi Li; Youcheng Huang; Shumin Jiang; Kun Wu; Li Yang (Chemical Engineering Journal, 2024)

Morphological Tracing and Functional Identification of Monosynaptic Connections in the Brain: A Comprehensive Guide - Yuanyuan Li; Yuanyuan Fang; Kaiyuan Li; Hongbin Yang; Shumin Duan; Li Sun (Neuroscience Bulletin, 2024)
Behavioral studies play a crucial role in unraveling the mechanisms underlying brain function. Recent advances in optogenetics, neuronal typing and labeling, and circuit tracing have facilitated the dissection of the neural circuitry involved in various important behaviors. The identification of monosynaptic connections, both upstream and downstream of specific neurons, serves as the foundation for understanding complex neural circuits and studying behavioral mechanisms. However, the practical implementation and mechanistic understanding of monosynaptic connection tracing techniques and functional identification remain challenging, particularly for inexperienced researchers. Improper application of these methods and misinterpretation of results can impede experimental progress and lead to erroneous conclusions. In this paper, we present a comprehensive description of the principles, specific operational details, and key steps involved in tracing anterograde and retrograde monosynaptic connections. We outline the process of functionally identifying monosynaptic connections through the integration of optogenetics and electrophysiological techniques, providing practical guidance for researchers.

Protective mechanism of carbon dioxide in pipelines for water containing typical corrosive anions - Shumin Yang; Mei Li; Tuodong Liu; Peizhi Gao; Huajun Zhang; Chao Yin; Yulin Tang (Process Safety and Environmental Protection, 2024)

The effect of L-cysteine on starch and protein degradation during barley germination - Shumin Hu; Qingqing Qin; Cui Zhang; Junhong Yu; Shuli Huang; Jia Liu; Zhaoxia Yang (Biotechnology Letters, 2024)

Identification of toxic metal contamination in surface sediments of the Xiaoqing River under a long-term perspective (1996–2020): Risks, sources and driving factors - Jiaying Yang; Lijun Ren; Chunyu Hua; Yueru Tian; Xian Yong; Shumin Fang (Environmental Research, 2024)

Conversion of flat to cylindrical hydrogel structures by asymmetric crosslinking and ionic exchange - Shumin Liang; Qing Chen; Xiaowen Huang; Bingbing Yang; Yicheng Guo; Panče Naumov; Lidong Zhang (Chemical Engineering Journal, 2024)

Indole-3 acetic acid negatively regulates rose black spot disease resistance through antagonizing the salicylic acid signaling pathway via jasmonic acid - Tingliang Xu; Xiaowen Zheng; Yi Yang; Shumin Yang; Xingwan Yi; Chao Yu; Le Luo; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Planta, 2024)

Characterization of Organosulfates (OSs) in typical urban areas in Eastern China: Source, Process, and Volatility - Yang Du; Hanxiong Che; Zier Bao; Yiliang Liu; Qing Li; Miao Hu; Jiawei Zhou; Shumin Zhang; Xiaojiang Yao; Quan Shi; Chunmao Chen; Yan Han; et al. (Atmospheric Research, 2024)

Enhanced denitrification performance of electrotrophic bio-cathode mediated by biochar and potential microbial mechanism - Meizhen Tang; Fei Lu; Zhina Guo; Shumin Yao; Shiqiang Ma; Yuewei Yang (Journal of Water Process Engineering, 2024)

Characterization of risks and pathogenesis of respiratory diseases caused by rural atmospheric PM2.5 - Ronghua Zhang; Xiaomeng Li; Xuan Li; Qin Zhang; Jiancai Tang; Zhenzhong Liu; Guiqin Song; Li Jiang; Fumo Yang; Jiawei Zhou; Hanxiong Che; Yan Han; et al. (Science of The Total Environment, 2024)

Using machine learning to trace the pollution sources of disinfection by-products precursors compared to receptor models - Yuan Xiao; Shunjun Ma; Shumin Yang; Huan He; Xin He; Cheng Li; Yuheng Feng; Bin Xu; Yulin Tang (Science of The Total Environment, 2024)

Bridging the gaps in cancer photothermal therapy through the intersection of nanotechnology and cell membrane coating - Shumin Yang; Huachun Pan; Blassan P. George; Xuanjian Fu; Hongwei Ma; Xiaojun Cai; Yang Chen; Qiang Cai; Quazi T.H. Shubhra (Chemical Engineering Journal, 2024)

Comparison of moving bed biofilm reactor and bio-contact oxidation reactor start-up with heterotrophic nitrification-aerobic denitrification bacteria and activated sludge inoculation under high ammonia nitrogen conditions - Qian Zhang; Huan Liu; Siyu Liang; Wang Chen; Senwen Tan; Chenxi Yang; Shumin Qin; Kun Long (Bioresource Technology, 2024)

Mechanism of inactivation of Aspergillus flavus spores by dielectric barrier discharge plasma - Yaxin Wang; Mingming Yu; Yanli Xie; Weibin Ma; Shumin Sun; Qian Li; Yuhui Yang; Xiao Li; Hang Jia; Renyong Zhao (Toxicon, 2024)

MBBR start-up with HN-AD bacteria inoculation: Comparative analysis in simulated and real wastewater for performance, microbial characteristics, and nitrogen removal mechanism - Qian Zhang; Siyu Liang; Senwen Tan; Wang Chen; Huan Liu; Chenxi Yang; Shumin Qin; Kun Long (Journal of Water Process Engineering, 2024)

Synergetic catalysis of Ni@C@CeO2 for driving ab/desorption of MgH2 at moderate temperature - Zhichao Yu; Xin Liu; Yang Liu; Yuan Li; Zhuohan Zhang; Kangli Chen; Shumin Han (Fuel, 2024)

Research on urban water security based on water poverty theory: a case study of lower yellow river cities - Yueru Tian; Chunyu Hua; Mengyuan Zhu; Zhaotong Fang; Xian Yong; Jiaying Yang; Shumin Fang; Lijun Ren (Stochastic Environmental Research and Risk Assessment, 2024)

Bioaugmentation using salt-tolerant bacteria in a dual-stage process for high-salinity wastewater treatment: Performance, microbial community, and salt-tolerance mechanism - Wang Chen; Shumin Qin; Chenxi Yang; Kun Long; Siyu Liang; Huan Liu; Senwen Tan; Qian Zhang (Journal of Water Process Engineering, 2024)

Photoinitiator-grafted polymer coating enable various hydrogels with strong resistance to both drying and swelling - Xiaobin Li; Jun Shi; Chenguang Kong; Cunzhi Li; Hangzhou Wang; Shumin Jiang; Yang Li (Chemical Engineering Journal, 2024)

Accuracy evaluation of ET and its components from three remote sensing ET models and one process based hydrological model using ground measured eddy covariance and sap flow - Xiaojin Li; Yonghui Yang; Xinyao Zhou; Shumin Han; Huilong Li; Yanmin Yang; Xiaohua Hao (Journal of Hydrology, 2023)

Distribution, sources, and risk analysis of heavy metals in sediments of Xiaoqing River basin, Shandong province, China - Shumin Fang; Zhaotong Fang; Chunyu Hua; Mengyuan Zhu; Yueru Tian; Xian Yong; Jiaying Yang; Lijun Ren (Environmental Science and Pollution Research, 2023)

Porous Graphitic phase carbon nitride/graphene oxide hydrogel microspheres for efficient and recyclable degradation of aflatoxin B1 in peanut oil - Shumin Sun; Jiayi Yang; Yajie Liu; Yanli Xie; Fred Mwabulili (Food Chemistry, 2023)

Storage stability and interfacial rheology analysis of high-internal-phase emulsions stabilized by soy hull polysaccharide - Hui Yang; Shengnan Wang; Yan Xu; Shumin Wang; Lina Yang; Hong Song; Yutang He; He Liu (Food Chemistry, 2023)

Model-Driven Deep-Learning-Based Underwater Acoustic OTFS Channel Estimation - Yuzhi Zhang; Shumin Zhang; Yang Wang; Qingyuan Liu; Xiangxiang Li (Journal of Marine Science and Engineering, 2023)
Accurate channel estimation is the fundamental requirement for recovering underwater acoustic orthogonal time–frequency space (OTFS) modulation signals. As the Doppler effect in the underwater acoustic channel is much more severe than that in the radio channel, the channel information usually cannot strictly meet the compressed sensing sparsity assumption in the orthogonal matching pursuit channel estimation algorithm. This deviation ultimately leads to a degradation in system performance. This paper proposes a novel approach for OTFS channel estimation in underwater acoustic communications, utilizing a model-driven deep learning technique. Our method incorporates a residual neural network into the OTFS channel estimation process. Specifically, the orthogonal matching pursuit algorithm and denoising convolutional neural network (DnCNN) collaborate to perform channel estimation. The cascaded DnCNN denoises the preliminary channel estimation results generated by the orthogonal matching pursuit algorithm for more accurate OTFS channel estimation results. The use of a lightweight DnCNN network with a single residual block reduces computational complexity while still preserving the accuracy of the neural network. Through extensive evaluations conducted on simulated and experimental underwater acoustic channels, the outcomes demonstrate that our proposed method outperforms traditional threshold-based and orthogonal matching pursuit channel estimation techniques, achieves superior accuracy in channel estimation, and significantly reduces the system’s bit error rate.

Electrochemical oxidation of chloramphenicol by modified Sm-PEG-PbO2 anodes: Performance and mechanism - Chaoyang Zhang; Conghao Gao; Shumin Yang; Xin He; Yue Chen; Xiao Qin; Yulin Tang (Chemosphere, 2023)

Mutagenicity of PM2.5 and Ethnic Susceptibility in Chengdu-Chongqing Economic Circle, China - Shumin Zhang; Qin Zhang; Xiaomeng Li; Ronghua Zhang; Hanxiong Che; Zhenzhong Liu; Dongmei Guo; Fumo Yang; Yang Chen (Science of The Total Environment, 2023)

Stimuli-activatable PROTACs for precise protein degradation and cancer therapy - Jing Gao; Lei Yang; Shumin Lei; Feng Zhou; Huijun Nie; Bo Peng; Tianfeng Xu; Xiaohua Chen; Xiaobao Yang; Chunquan Sheng; Yu Rao; Kanyi Pu; et al. (Science Bulletin, 2023)

Nitrogen and Sulfur Co-doped Carbon Dots as a Turn-Off Fluorescence Probe for the Detection of Cerium and Iron - Lichao Pei; Weiyuan Zhang; Shuqin Yang; Kangli Chen; Xiaoxuan Zhu; Yan Zhao; Shumin Han (Journal of Fluorescence, 2023)

Interaction of earthquake-triggered landslides and local relief: Evidence from the 2008 Wenchuan earthquake - Yigen Qin; Dongli Zhang; Wenjun Zheng; Jingjun Yang; Gan Chen; Lei Duan; Shumin Liang; Hui Peng (Landslides, 2023)

Study on the whole process application of advanced grouting pipe shed support under urban complex stratum conditions - Yuan Mei; Xin Ke; Dong-bo Zhou; Shumin Zhang; Tong Yang (Geomechanics for Energy and the Environment, 2023)

Exploring the driving factors of haze events in Beijing during Chinese New Year holidays in 2020 and 2021 under the influence of COVID-19 pandemic - Lining Luo; Xiaoxuan Bai; Yunqian Lv; Shuhan Liu; Zhihui Guo; Wei Liu; Yan Hao; Yujiao Sun; Jiming Hao; Kai Zhang; Hongyan Zhao; Shumin Lin; et al. (Science of The Total Environment, 2023)

Prediction of the freshness of horse mackerel (Trachurus japonicus) using E-nose, E-tongue, and colorimeter based on biochemical indexes analyzed during frozen storage of whole fish - Hongyue Li; Yang Wang; Jiaxin Zhang; Xuepeng Li; Jinxiang Wang; Shumin Yi; Wenhui Zhu; Yongxia Xu; Jianrong Li (Food Chemistry, 2023)

Mixing-layer depth-based backwards trajectory analysis of the sources of high O3 concentrations at the Wutaishan station, North China - Shiming Yan; Xingai Gao; Kunning Pei; Hongping Sun; Yan Wang; Fengsheng Zhang; Ying Li; Shumin Wang; Ling Chen; Jian Dong; Feihong Yang (Atmospheric Pollution Research, 2023)

P62/SQSTM1 upregulates NQO1 transcription via Nrf2/Keap1a signaling pathway to resist microcystins-induced oxidative stress in freshwater mussel Cristaria plicata - Jielian Wu; Shumin Hou; Lang Yang; Yanrui Wang; Chungen Wen; Yuping Guo; Shanshan Luo; Haihong Fang; He Jiao; Hui Xu; Shuangping Zhang (Aquatic Toxicology, 2023)

Effect of Fluoxetine on the Surface Behavior of the Lipid Monolayers at Different Surface Pressures - Bin Xie; Shumin Yang (The Journal of Membrane Biology, 2023)

H2O2 accumulation plays critical role in black spot disease resistance in roses - Shumin Yang; Tingliang Xu; Yi Yang; Wenyue Pei; Le Luo; Chao Yu; Jia Wang; Tangren Cheng; Qixiang Zhang; Huitang Pan (Horticulture, Environment, and Biotechnology, 2023)

Distribution Characteristics of Nutritional Elements and Combined Health Risk of Heavy Metals in Medicinal Tea from Genuine Producing Area of China - Ming Sui; Dandan Kong; Haonan Ruan; Xinqi Sun; Wei Gu; Mengyue Guo; Shumin Ding; Meihua Yang (Biological Trace Element Research, 2023)

Research progress of ochratoxin a bio-detoxification - Fred Mwabulili; Yanli Xie; Qian Li; Shumin Sun; Yuhui Yang; Weibin Ma (Toxicon, 2023)

Understanding and revealing the intrinsic impacts of the COVID-19 lockdown on air quality and public health in North China using machine learning - Yunqian Lv; Hezhong Tian; Lining Luo; Shuhan Liu; Xiaoxuan Bai; Hongyan Zhao; Kai Zhang; Shumin Lin; Shuang Zhao; Zhihui Guo; Yifei Xiao; Junqi Yang (Science of The Total Environment, 2023)

Deep Learning-Based Signal Detection for Underwater Acoustic OTFS Communication - Yuzhi Zhang; Shumin Zhang; Bin Wang; Yang Liu; Weigang Bai; Xiaohong Shen (Journal of Marine Science and Engineering, 2022)
Orthogonal time frequency space (OTFS) is a novel two-dimensional (2D) modulation technique that provides reliable communications over time- and frequency-selective channels. In underwater acoustic (UWA) channel, the multi-path delay and Doppler shift are several magnitudes larger than wireless radio communication, which will cause severe time- and frequency-selective fading. The receiver has to recover the distorted OTFS signal with inter-symbol interference (ISI) and inter-carrier interference (ICI). The conventional UWA OTFS receivers perform channel estimation explicitly and equalization to detect transmitted symbols, which requires prior knowledge of the system. This paper proposes a deep learning-based signal detection method for UWA OTFS communication, in which the deep neural network can recover the received symbols after sufficient training. In particular, it cascades a convolutional neural network (CNN) with skip connections (SC) and a bidirectional long short-term memory (BiLSTM) network to perform signal recovery. The proposed method extracts feature information from received OTFS signal sequences and trains the neural network for signal detection. The numerical results demonstrate that the SC-CNN-BiLSTM-based OTFS detection method performs with a lower bit error rate (BER) than the 2D-CNN, FC-DNN, and conventional signal detection methods.

A stable method for Agrobacterium-mediated transformation of Mentha piperita and Mentha canadensis using internodal explants - Xu Yu; Zequn Chen; Shumin Li; Xiwu Qi; Hailing Fang; Yang Bai; Li Li; Dongmei Liu; Qun Liu; Weilin Li; Chengyuan Liang (In Vitro Cellular & Developmental Biology - Plant, 2022)

Pathological Networks Involving Dysmorphic Neurons in Type II Focal Cortical Dysplasia - Yijie Shao; Qianqian Ge; Jiachao Yang; Mi Wang; Yu Zhou; Jin-Xin Guo; Mengyue Zhu; Jiachen Shi; Yiqi Hu; Li Shen; Zhong Chen; Xiao-Ming Li; et al. (Neuroscience Bulletin, 2022)

First report of Colletotrichum queenslandicum causing leaf anthracnose on Dracaena cambodiana in China - Shumin Wang; Meijiao Hu; Xiangxiang Qu; Jinyu Yang; Zhaoyin Gao; Shuming Wang; Zhiqiang Liu; Min Li (Journal of General Plant Pathology, 2022)

Shifting from homogeneous to heterogeneous surfaces in estimating terrestrial evapotranspiration: Review and perspectives - Yuanbo Liu; Guoyu Qiu; Hongsheng Zhang; Yonghui Yang; Yinsheng Zhang; Quan Wang; Wenzhi Zhao; Li Jia; Xibin Ji; Yujiu Xiong; Chunhua Yan; Ning Ma; et al. (Science China Earth Sciences, 2022)

Brain-wide Mapping of Mono-synaptic Afferents to Different Cell Types in the Laterodorsal Tegmentum - Xiaomeng Wang; Hongbin Yang; Libiao Pan; Sijia Hao; Xiaotong Wu; Li Zhan; Yijun Liu; Fan Meng; Huifang Lou; Ying Shen; Shumin Duan; Hao Wang (Neuroscience Bulletin, 2019)

LncRNA MALAT1 protects human umbilical vein endothelial cells against ox-LDL triggered cell death through regulation of MGP - Xia Wang; Hongqin Zhao; Shaonan Yang; Xiaojun Shao; Shumin Nie; Xudong Pan (Molecular & Cellular Toxicology, 2019)

Over-expression of a plasma membrane H+-ATPase SpAHA1 conferred salt tolerance to transgenic Arabidopsis - Yafei Fan; Shumin Wan; Yingshuo Jiang; Youquan Xia; Xiaohui Chen; Mengze Gao; Yuxin Cao; Yuehua Luo; Yang Zhou; Xingyu Jiang (Protoplasma, 2018)

Imaging the dynamic deposition of cell wall polymer in xylem and phloem in Populus × euramericana - Kexia Jin; Xinge Liu; Kun Wang; Zehui Jiang; Genlin Tian; Shumin Yang; Lili Shang; Jianfeng Ma (Planta, 2018)

The Sesuvium portulacastrum Plasma Membrane Na+/H+ Antiporter SpSOS1 Complemented the Salt Sensitivity of Transgenic Arabidopsis sos1 Mutant Plants - Yang Zhou; Xiaochang Yin; Shumin Wan; Yanping Hu; Qing Xie; Ruimei Li; Baibi Zhu; Shaoping Fu; Jianchun Guo; Xingyu Jiang (Plant Molecular Biology Reporter, 2018)

Macroautophagy occurs in distal TMV-uninfected root tip tissue of tomato taking place systemic PCD - Shumin Zhou; Qiang Hong; Yang Li; Qi Li; Ruisha Li; Hongli Zhang; Mao Wang; Xiaojun Yuan (Protoplasma, 2018)

Spy1 participates in the proliferation and apoptosis of epithelial ovarian cancer - Shumin Lu; Rong Liu; Min Su; Yingze Wei; Shuyun Yang; Song He; Xia Wang; Fulin Qiang; Chen Chen; Shuyang Zhao; Weiwei Zhang; Pan Xu; et al. (Journal of Molecular Histology, 2016)

Characteristics and Driving Factors of Drainage Water in Irrigation Districts in Arid Areas - Shumin Han; Qiuli Hu; Yonghui Yang; Jiusheng Wang; Ping Wang; Quan Wang (Water Resources Management, 2015)

Expression and clinical role of TCTP in epithelial ovarian cancer - Chen Chen; Yan Deng; Minhui Hua; Qinghua Xi; Rong Liu; Shuyun Yang; Jian Liu; Jianxin Zhong; Meilan Tang; Shumin Lu; Zhimei Zhang; Xiao Min; et al. (Journal of Molecular Histology, 2015)

Complex structures of transgene rearrangement implicate novel mechanisms of RNA-directed DNA methylation and convergent transcription - Zheng Liu; Shuangcheng Gao; Shumin Zhang; Shangjun Yang; Ning Sun (Genes & Genomics, 2014)

Expression, Purification and Functional Reconstitution of Slack Sodium-Activated Potassium Channels - Yangyang Yan; Youshan Yang; Shumin Bian; Fred J. Sigworth (The Journal of Membrane Biology, 2012)

Treadmill training prevents bone loss by inhibition of PPARγ expression but not promoting of Runx2 expression in ovariectomized rats - Yongjie Chen; Shouhui Wang; Shumin Bu; Yingjie Wang; Yushuang Duan; Shaofeng Yang (European Journal of Applied Physiology, 2011)

Decreased surfactant protein B expression in mice derived completely from embryonic stem cells - Shumin Gao; Xiaohui Wen; Rongrong Yang; Keqian Di; Jun Tong; Xiangyun Li (In Vitro Cellular & Developmental Biology - Animal, 2008)